Lecturenotes9-11March2011

# Lecturenotes9-11March2011 - Section 4.6 Change of Basis Let...

This preview shows pages 1–3. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Section 4.6 Change of Basis Let B = { v 1 ,v 2 ,...,v n } be a basis for a finite dimensional vector space V. Let v ∈ V then we can express v as v = c 1 v 1 + c 2 v 2 + ... + c n v n . Recall the coordinate vector of v, which was denoted as ( v ) B = ( c 1 ,c 2 ,...,c n ) . In this section we will see how to coordinate vectors are changing with the change of basis. Example: B = { (1 , 0) , (0 , 1) } and B = { (1 , 1) , (2 , 1) } are bases for R 2 . Consider u = (2 , 3) ∈ R 2 . Then we have ( u ) B = (2 , 3) and ( u ) B = (4 ,- 1) What is the relation between the coordinates of a vector with respect to different bases? Solution: If we change the basis for a vector space V from an old basis B= { u 1 ,u 2 ,u 3 ,...,u n } to a new basis B = { u 1 ,u 2 ,...,u n } , then for each vector v in V, the old coordinate vector [ v ] B is related to the new coordinate vector [ v ] B by the equation [ v ] B = P [ v ] B where the columns of P are the coordinate vectors of the new basis vectors relative to the old basis; that is, the column vectors of P are [ u 1 ] B , [ u 2 ] B ,..., [ u n ] B P B → B = [[ u 1 ] B , [ u 2 ] B ,..., [ u n ] B ] , [ v ] B = P B → B [ v ] B P B → B = [[ u 1 ] B , [ u 2 ] B ,..., [ u n ] B ] , [ v ] B = P B → B [ v ] B Example: Consider the bases B = { u 1 ,u 2 ,u 3 } and B = { u 1 ,u 2 ,u 3 } for R 3 , where u 1 = (- 3 , ,- 3) ,u 2 = (- 3 , 2 ,- 1) ,u 3 = (1 , 6 ,- 1) and u 1 = (- 6 ,- 6 , 0) ,u 2 = (- 2 ,- 6 , 4) ,u 3 = (- 2 ,- 3 , 7) (a) Find the transition matrix from B to B (b) Compute the coordinate vector [ w ] B where w = (- 5 , 8 ,- 5) and use part (a) to compute [ w ] B . Solution: (a) We want P B → B = [[ u 1 ] B , [ u 2 ] B , [ u 3 ] B ] ; [ u 1 ] B : Consider u 1 = c 1 u 1 + c 2 u 2 + c 3 u 3 , from here we get a linear system of equations:- 6 c 1- 2 c 2- 2 c 3 =- 3- 6 c 1- 6 c 2- 3 c 3 = 0 4 c 2 + 7 c 3 =- 3 1 Solving this system gives c 1 = 3 4 ,c 2 =- 3 4 ,c 3 = 0 , hence [ u 1 ] B = ( 3 4 ,- 3 4 , 0) . [ u 2 ] B : Consider u 2 = c 1 u 1 + c 2 u 2 + c 3 u 3 , from here we get a linear system of equations:- 6 c 1- 2 c 2- 2 c 3 =- 3- 6 c 1- 6 c 2- 3 c 3 = 2 4 c 2 + 7 c 3 =- 1 Solving this system gives c 1 = 3 4 ,c 2 =- 17 12 ,c 3 = 2 3 , hence [ u 2 ] B = ( 3 4 ,- 17 12 , 2 3 ) . [ u 3 ] B : Consider u 3 = c 1 u 1 + c 2 u 2 + c 3 u 3 , from here we get a linear system of equations:- 6 c 1- 2 c 2- 2 c 3 = 1- 6 c 1- 6 c 2- 3 c 3 = 6 4 c 2 + 7 c 3 =- 1 Solving this system gives c 1 = 1 12 ,c 2 =- 17 12 ,c 3 = 2 3 , hence [ u 3 ] B = ( 1 12 ,- 17 12 , 2 3 ) ....
View Full Document

## This document was uploaded on 04/26/2011.

### Page1 / 8

Lecturenotes9-11March2011 - Section 4.6 Change of Basis Let...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online